Plea Bargaining Dalam Penyelesaian Tindak Pidana Korupsi Pada Sistem Peradilan Pidana - Sitohang, Kalvin A; Simangunsong, Frans (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Corruption remains a serious threat to Indonesia's state finances and economic stability. Lengthy and complicated judicial processes often hinder efforts to recover state losses and create a backlog of cases in the courts. Plea bargaining offers an alternative means of resolving cases, allowing prosecutors and defendants to reach agreements on lighter sentences in exchange for guilty pleas and the full return of assets. This mechanism not only speeds up the judicial process, but also reduces the burden on the prison budget, alleviates the backlog of cases, and increases the effectiveness of asset recovery. This study uses a normative legal approach by analyzing legislation, the draft Criminal Procedure Code, and existing justice collaborator practices. The results show that plea bargaining can be integrated into the Indonesian criminal justice system through a “special channel” with strict judicial oversight, particularly in cases of minor to moderate corruption, without compromising the principles of justice and deterrence. Measured implementation will support the principles of swift, simple, and inexpensive justice while prioritizing the recovery of state losses.